The precedent of the Council of State in the sources of administrative law (2019)
This article deals with reflecting on the role of the judicial precedent of the Council of State in relation to the system of sources of Colombian administrative law. Therefore, its main purpose is to provide elements of analysis that contribute to elucidating its role as the main source. To do this, we start by contextualizing, defining and differentiating notions such as jurisprudence and precedent. Then, the evolution of these concepts in the Constitutional Court and the Supreme Court of Justice is reviewed in order to evaluate its use in the Council of State’s decisions. Regarding the latter, particular attention is given to the judgements of jurisprudential unification, which have a binding force of legal status. However, for systematic reasons it is argued that, in this “jurisdiction”, they are not the only ones that set a judicial precedent.